Brønsted base-catalyzed annulation of allyl ketones and alkynyl 1, 2-diketones. Issue 34 (9th April 2018) - Kong, Xiangwen; Song, Jinshuai; Liu, Jian; Meng, Miao; Yang, Shuang; Zeng, Min; Zhan, Xinyue; Li, Chunsen; Fang, Xinqiang
Abstract : The Cs2 CO3 -catalyzed reaction of allyl ketones and alkynyl 1, 2-diketones affords a series of 2-acyloxycyclopent-3-enones under mild conditions. A unique α-selective addition/aldol reaction/C–C bond cleavage mechanism was proposed and supported by DFT calculations. Abstract : The discovery of new reaction modes mediated by easily available substrates is an important research topic in organic synthesis. Allyl ketones and related compounds have been demonstrated to undergo γ- or α-selective additions to different electrophiles. We disclose here the Brønsted base-catalyzed reaction of allyl ketones and alkynyl 1, 2-diketones, which undergo a unique α-selective addition/intramolecular aldol-type annulation/C–C bond cleavage process, and a series of 2-acyloxycyclopent-3-enones can be obtained under very mild conditions.